Implementasi Quality Information Management Pada Lean Manufacturing System - Adi Rusdi Widya; Sugeng Budi Raharjo (Prosiding Sains dan Teknologi, 2022)
Industrial development in the era of Industry Revolution 4.0 (IR4.0) requires the company's readiness to run its business in order to remain competitive, strategies and efforts are needed to improve company performance, in carrying out Lean Manufacturing (LM) making maximum use of resources and minimizing waste and eliminating non-existent activities. value-added. One aspect that is focused on increasing productivity is availability, performance, and quality. Overall Equipment Effectiveness (OEE) is a measurement method that functions to determine the effectiveness of the use and utilization of machines, equipment, time and materials in a production process used by management as an approach in solving equipment effectiveness problems. Quality Information Management (QIM) to evaluate and verify the benefits gained by improving process maturity levels, process models and product quality models with improved, high-quality software products that are delivered on time and at lower costs. In its application, OEE can be integrated with the use of Radio Frequency Identification (RFID), Quick Response code (QR) and Barcode. This paper describes the implementation and development of research on QIM, widespread use of ICT in production, can connect physical objects with digital systems and integrate them. The use of QIM can increase flexibility and productivity and be able to track and trace in the event of an abnormality and prevent operation errors. Keywords: IR.4.0, lean manufacturing, QIM, OEE, RFID, QR, Bar Code